ETIKA PENDIDIK DAN PESERTA DIDIK DALAM PENDIDIKAN ISLAM (ANALISIS KITAB AL-MANHAJ AL-SAWI SYARH USHUL THARIQAH AL-SADAH AL-BA’ALAWI KARYA HABIB ZEIN BIN IBRAHIM BIN SUMAITH) - fatihna, khulqi; Muhammad Syauqillah (Journal Islamic Studies, 2024)
This research discusses the importance of ethics for educators and students based on the views of Habib Zein bin Sumaith in the book al-Manhaj al-Sawi Syarh Ushul Thariqah al-Sadah al-Ba'alawi. The purpose of this study is to examine the ethics that must be owned by educators and students according to the book. This research uses a qualitative method with a literature study approach, and the data analyzed comes from primary and secondary sources. The results show that the ethics of educators include justice, honesty, wisdom, zuhud, tawaduk, and gentleness towards students. While the ethics of learners include heart cleansing, good learning goals, tawaduk, and simplicity in life.